Uncommon histopathological oral findings in an autopsied infant with cystic fibrosis. - Eduardo Rodrigues Fregnani; Ana Lúcia Carrinho Ayrosa Rangel; Fábio Augusto Ito; Ilana Halpern; Paulo Hilário Nascimento Saldiva; Pablo Agustin Vargas (Universidade Estadual de Campinas, 2015)
Cystic Fibrosis or Mucoviscidosis is a hereditary genetic disease that attacks mainly children and young adults. It is characterized by a general dysfunction of the exocrine glands. We described uncommon histopathological findings in tongue and sublingual gland of a patient with Cystic Fibrosis. The 11-month-old female patient, had a history of repeated bronchopneumonia, chronic diarrhea and malnutrition during internment. On investigation, a high dose of chlorine was detected in the perspiration, and the diagnosis of Mucoviscidosis was made. The patient did not respond to treatment, and died in August 1997. During the autopsy, was noted lungs with bronchiectasis and bronchopneumonia with abscesses, stomach containing a large quantity of thick mucus and hepatomegaly. The organ fragments were fixed in formalin and the histological cuts were stained with H/E, Gomori-Grocott, ZiehlNeelsen and Brown-Hopps. Microscopically, the lung tissue showed chronic bronchitis and abscesses with hemorrhagic areas, and in the pancreas the ducts were dilated and filled with thick mucus, as well as evident cystic areas. On the tongue and sublingual gland we noted dilated ducts full of thick mucus and cystic areas. Furthermore, on the tongue areas with squamous ductal metaplasia and in the sublingual gland periductal fibrosis were found.